Profil Kemandirian Belajar Peserta Didik Kelas V SDN Panggung Lor - Kusumowardani, Diyah; Wijayanti, Arfilia; Prayito, Muhammad (MASALIQ, 2023)
This study aims to describe the profile of learning independence of fifth grade students at SDN Panggung Lor. The research subjects were students of class V at SDN Panggung Lor, totaling 29 children. The approach used in this research is qualitative with descriptive research type. Data collection techniques through observation, interviews, questionnaires and documentation. The calculation of the questionnaire method uses a Likert scale with the formula P = F/N x 100% and is categorized into a rating scale. Based on the results of the study, it can be concluded that the learning independence of fifth grade students at SDN Panggung Lor is developing well and is very enthusiastic so that the interaction of the teaching and learning process can take place as expected. This can be seen from the average learning independence questionnaire results of 76.076% with good criteria.